2022
DOI: 10.3389/fgene.2022.1014836
|View full text |Cite
|
Sign up to set email alerts
|

Screening and functional analysis of the differential peptides from the placenta of patients with healthy pregnancy and preeclampsia using placental peptidome

Abstract: Molecular peptides play an extensive range of functions in the human body. However, no previous study has performed placental peptidome profiling. In the present study, 3,941 peptides from human placental tissues were identified using peptidomics. Compared to healthy pregnant women, there were 87 and 129 differentially expressed peptides (DEPs) in the mild and severe preeclampsia groups, respectively. In the mild PE group, 55 and 34 DEPs had high and low expressions, respectively. In comparison, in the severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…At present, most studies have confirmed that the TGF-β1/SMAD signaling pathway is involved in the development of PE, and it is an integral part of PE treatment. For example, placenta-derived peptide regulates placental function during PE progression via the TGF-β1/SMAD signaling pathway ( 178 ). In addition, miR-140-5p may be involved in PIH progression by regulating the TGF-β1/SMAD signaling pathway ( 179 ).…”
Section: The Signaling Pathways Involved In Syncytializationmentioning
confidence: 99%
“…At present, most studies have confirmed that the TGF-β1/SMAD signaling pathway is involved in the development of PE, and it is an integral part of PE treatment. For example, placenta-derived peptide regulates placental function during PE progression via the TGF-β1/SMAD signaling pathway ( 178 ). In addition, miR-140-5p may be involved in PIH progression by regulating the TGF-β1/SMAD signaling pathway ( 179 ).…”
Section: The Signaling Pathways Involved In Syncytializationmentioning
confidence: 99%